The mythical nature of MDG7c to Kenya's arid and semi-arid lands (ASALS) - Augustine Afullo; B. Danga (2013)
Achieving millennium development Goal 7c (MDG7c) on access to improved water seems doubtful for Kenya’s Arid and semi-Arid lands (ASALs). This work sought to investigate the progress made in Kenya’s ASALs towards achieving the MDG7c, with a view to establishing whether it is achievable with the short time left. Heads of 4872 household (HH) in six ASAL counties of Kenya were identified using Probability and non-probability sampling techniques, and pretested structured questionnaire, Key Informant Interviews (KII) and Focused Group Discussions (FGD) administered to them. There are at least six different water sources, with 43% HHs using natural water sources. Whereas 89% of the world’s population had attained the MDG goal on access to improved water source, Sub-Saharan Africa is only 61% while Kenya’s ASALs rate even worse, with only 33% of all HHs have attained the MDG7 on improved water, rendering its achievement a myth in these ASAL areas.